Kushner Does Milton: Wrestling with the Revolutionary Poet in Angels in America and Other Plays. - Conti, Brooke (Contemporary Literature)
In the article, the author examines the influence of John Milton's "Paradise Lost" in the works of Tony Kushner, particularly "Angels in America." Topics include the subjects allegedly borrowed from "Paradise Lost" like cosmology, angels and the depiction of humanity's place in creation and the critics on "Angels in America" on topics like capitalist individualism and Jewish identity.